(untitled) (Research, Society and Development, 2022)
Objective: to describe trends in Brazilian scientific production in the development of ethnographic research with technology-dependent children. Method: The search was carried out in the Database of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES) in June 2018 and updated in April and May 2022. The terms used were “ethnography” AND "child". Eleven articles were selected for full reading. Results: It was possible to identify the thematic trend focused on studies in the area of education, among the productions in the health area, nursing studies stand out. In addition, studies approach children with special health needs without using this terminology, which makes their identification difficult, which becomes focused on the specific pathology of the child. Conclusion: This study pointed out that Brazilian ethnographic studies carried out with technology-dependent children are still incipient, although the specificities of this population corroborate the use of this method to understand issues beyond the biological context, also considering sociocultural aspects and giving voice to this specific group.